Formal Diels-Alder reactions of chalcones and formylcyclopropanes catalyzed by chiral N-heterocyclic carbenes - Lv, Hui (2014)
Highly enantioselective (formal) hetero-Diels–Alder reactions between chalcones and formylcyclopropanes are disclosed. The challenging N-heterocyclic carbene (NHC)-bounded enolate intermediates from formylcyclopropanes were captured for new C–C bond forming reactions. The reaction products were obtained with high diastereo- and enantioselectivities and could be easily transformed to optically pure multisubstituted cyclohexane derivatives.